2018
DOI: 10.1021/acs.energyfuels.8b00756
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Chemical Absorption–Biological Reduction System for NO Removal: System Start-up and Optimal Operation Mode

Abstract: A novel chemical absorption–biological reduction (CABR) integrated process, employing Fe­(II)­EDTA as an enhanced absorbent, is a promising technology for nitrogen oxides removal. In this work, we developed a new two-stage CABR system applying a mixed cultivation model of denitrifying bacteria and iron-reducing bacteria, which consists of a sieve-plate tower and a bioreduction tower to separate the absorption and reduction processes. The start-up period of the two-stage system was shortened to 19 days, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…For decades, the main anthropogenic source of NO x has been emissions from industrial boilers (kilns). , Some technologies have been introduced for controlling flue gas from boilers (kilns) and reducing the release of NO x , such as selective catalytic reduction (SCR), low-NO x burners, absorption, adsorption, and selective noncatalytic reduction (SNCR). , However, these methods can have a high cost, low removal efficiency, and cause secondary pollution . The biological treatment of industrial flue gas for NO x removal was proposed in the 1980s as a low-cost and environmentally sustainable approach, and related studies have focused mainly on isolating denitrifying bacteria and improving biological reactors. , Wang et al studied denitrifying bacteria in bioreactors for landfill leachate treatment and found that the main bacteria in the bioreactor varied with changes in the hydraulic loading.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For decades, the main anthropogenic source of NO x has been emissions from industrial boilers (kilns). , Some technologies have been introduced for controlling flue gas from boilers (kilns) and reducing the release of NO x , such as selective catalytic reduction (SCR), low-NO x burners, absorption, adsorption, and selective noncatalytic reduction (SNCR). , However, these methods can have a high cost, low removal efficiency, and cause secondary pollution . The biological treatment of industrial flue gas for NO x removal was proposed in the 1980s as a low-cost and environmentally sustainable approach, and related studies have focused mainly on isolating denitrifying bacteria and improving biological reactors. , Wang et al studied denitrifying bacteria in bioreactors for landfill leachate treatment and found that the main bacteria in the bioreactor varied with changes in the hydraulic loading.…”
Section: Introductionmentioning
confidence: 99%
“…Xing et al studied the microorganisms involved in the micro-electrolysis and autotrophic denitrification processes by high-throughput sequencing and found that β-, γ-, and α- Proteobacteria were the dominant genera. However, biological approaches have been limited by their low efficiency, which is caused by the low solubility of NO in liquid and the higher proportion of NO in NO x from flue gas. , Therefore, a new integrated technology has been developed that combines complex absorption processes with biological reduction. , Ferrous ethylenediaminetetraacetic acid (EDTA-Fe II ) had been reported to rapidly form complexes with NO, which resolves the issues associated with the low gas–liquid mass transfer efficiency of NO . An electrobiofilm was subsequently introduced and has been demonstrated to further strengthen the regeneration rate of EDTA-Fe II , as it not only forms complexes with NO to generate EDTA-Fe II -NO but also oxidizes into EDTA-Fe III by oxygen in the flue gas (approximately 9% content in the flue gas in industrial boilers) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a cost-effective and eco-friendly process for nitric oxide (NO) removal, the chemical absorption-biological reduction (CABR) flue gas denitrification technology is based on wet absorption of NO using ferrous complexes, especially ferrous ethylenediaminetetraacetate [Fe(II)EDTA], to improve the NO absorption into scrubbing liquid, and biological reduction regeneration of chelate agent to reduce operation costs (Zhang et al 2014, 2018; Zhao et al 2016). However, typical flue gas after the traditional flue gas desulfurization process is estimated to contain 3–8% (v/v) O 2 (Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, selective catalytic reduction (SCR) and selective non-catalytic reduction (SNCR) are conventional technologies for postcombustion NO x control, and several novel solid or liquid sorbents and catalysts have been developed for NO x reduction. Assuming that the emission of NO x from oxy-fuel flue gas is controlled using traditional SCR or SNCR technology, this will add to the investment and operation costs because an additional flue gas denitrification device is required in an oxy-fuel plant. There is the possibility of using the existing CO 2 compression and purification units (CPUs) as a cleaning step for NO x removal instead of the traditional flue gas denitrification device.…”
Section: Introductionmentioning
confidence: 99%